2021
DOI: 10.1111/ans.16743
|View full text |Cite
|
Sign up to set email alerts
|

Lateral versus cross pinning in paediatric supracondylar humerus fractures: a meta‐analysis of randomized control trials

Abstract: Background Supracondylar humerus fractures are common in children. Percutaneous pinning remains the mainstay in treatment; however, there is lack of consensus on the optimal configuration: lateral‐only pinning or cross pinning. This study aims to investigate the differences in clinical and surgical outcomes between lateral‐only and cross‐pinning paediatric supracondylar humerus fractures. Methods A systematic search was performed using Medline Ovid, Embase and Cochrane databases for relevant randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…17 Another recent meta-analysis by Kwok et al including 11 studies reported that lateral pinning is associated with higher loss of reduction and had lower risk of iatrogenic ulnar nerve injury. 18 In our study, the radiologic and functional outcomes were almost similar between the groups. But there was difference between two techniques in safety of ulnar nerve as there were four injuries to ulnar nerve in cross pin group (4.2%) and none in lateral pin technique which were neuropraxia type and recovered fully in 3 months.…”
Section: Discussionsupporting
confidence: 62%
“…17 Another recent meta-analysis by Kwok et al including 11 studies reported that lateral pinning is associated with higher loss of reduction and had lower risk of iatrogenic ulnar nerve injury. 18 In our study, the radiologic and functional outcomes were almost similar between the groups. But there was difference between two techniques in safety of ulnar nerve as there were four injuries to ulnar nerve in cross pin group (4.2%) and none in lateral pin technique which were neuropraxia type and recovered fully in 3 months.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, pin tract infection occurred in one case of the external fixation group, which may be related to the local skin tension and the larger diameter of the Schanz screw. Although some studies have shown that the mechanical effect of inserting anti-rotating Kirschner wire from the inside is better [ 32 ], there is still a risk of iatrogenic ulnar nerve injury [ 33 ]. Therefore, we recommended the lateral entry anti-rotating Kirschner wire.…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses found comparable construct stability and functional outcomes between both pinning configurations and recommended lateral pinning as a result of decreased risk ulnar nerve injury [ 9 , 14 , 15 ]. Some did not prioritize the fixation techniques because of a less fixation stability of lateral pinning but a higher risk of ulnar nerve risk of crossed pinning [ 7 , 12 , 13 ]. The inconsistency may be caused by the inclusion of non-randomized controlled trials (non-RCTs), i.e., retrospective case–control or prospective cohort studies, that have a low evidence level or a small number of eligible RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses comparing the efficacy and safety of crossed pin fixation versus lateral pin fixation in children with SCHFs have been published [7,[9][10][11][12][13][14][15]. Yet, the results are mixed.…”
Section: Introductionmentioning
confidence: 99%